Trabalho e trabalhadores das confecções em Santo Antônio do Sudoeste PR - Costa, Gilvana Machado (2015)
This research aims to describe and understand the ways of living and working of the workers involved in production dynamics in the manufacturing sector. The survey covers the southwest region of Paraná, more specifically the city of Santo Antonio Southwest, for its changes in the production of clothing from the 1960s to the year 2013. Some of the workers have in their career working in the field and later industrial work. This experience shows striking changes, especially when they are followed by illness. This result is a form of work organization, pace, pressures and extended daily hours for overtime and poor working conditions. By analyzing the Journal of Beltrao circulating in the southwest region, narratives contradict the speech to some extent convincing. Therefore, the analysis set up in denunciation of these working conditions. Because in addition to not allow the worker to overcome the production process keeps subordinate. For this research it was necessary to the production and analysis of interviews with workers, two editions of the Journal of Beltrao, and Ipardes data